Conditions of large unitary (K, Na)NbO3 system single crystals for rapid solid-state crystal growth method. (1st March 2023) - Morimoto, Takaaki; Shimono, Seiya; Yoshiichi, Yuto; Kishimura, Hiroaki; Ishii, Keisuke
Abstract: To expand the process window for the rapid solid-state crystal growth (RSSCG) method, through which large unitary single crystals of a (K0.5 Na0.5 )NbO3 (KNN) system can be synthesized in a short time, we varied the dominant fabrication parameters, the B-site excess ratio and the Bi2 O3 content, over a range wider than that utilized in previous studies. Unitary single crystals were obtained at the B-site excess ratios of 0.75%–1.75%; particularly, 1.00% and 1.25% were found to be suitable for the synthesis. Electron spin resonance analysis showed that the concentration of oxygen vacancies increased with increasing B-site excess ratios and decreased with increasing amount of added Bi2 O3 in the calcined powder. The optimization of the critical driving force for crystal growth by controlling oxygen vacancy concentration was found to be key to growing the large unitary single crystals appropriately by the RSSCG method.